ANALISIS LAGU “SELALU ADA DI NADIMU” KARYA LALEIMANINO MENGGUNAKAN PENDEKATAN MIMETIK - Fauzi; Yahya, Wildan Albiruni; Yunus, Syarifudin (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study aims to analyze the song "Selalu Ada di Nadimu" by Laleilmanino using the mimetic approach in literary criticism. The mimetic approach views a work of art as a reflection of social reality and human experience, so this analysis focuses on how the song’s lyrics represent the emotional relationship between parents and children as well as the strong family values in Indonesian society. The song is considered a reflection of the creator’s personal experience as well as a broader social reality, especially regarding the hopes and prayers of parents for their children to remain strong in facing life’s challenges. The method used is qualitative descriptive with content analysis of the lyrics as the main data. The results show that "Selalu Ada di Nadimu" functions not only as an aesthetic work of art but also as a medium of social reflection conveying moral messages and real-life values through symbolism and metaphors in its lyrics. Thus, the song reinforces the function of music as a communication tool capable of portraying and strengthening the social and emotional experiences of its listeners.